Estimation of Global Solar Radiation Using Empirical Model on Meteorological Parameters at Simara Airport, Bara, Nepal - Awasthi, Janaki; Poudyal, Khem Narayan (Journal of the Institute of Engineering, 2018)
This research work purpose to estimate the daily global solar radiation (GSR) using CMP6 pyranometer at low altitude of Simara Airport (lat. 27°9’33” N and long. 84°58’48” E, Alt.137m respectively). The measured data is used to study the diurnal, monthly, and seasonal variation of GSR. The maximum and minimum value of GSR is found at the spring and winter season respectively. A number of multi linear regression equations were developed to predict the relationship between GSR with one or more combinations of meteorological parameters using the regression technique and calculate the empirical constants from Tiwari & Sangeeta model which is the best empirical model among other tested models. The empirical constants and sunshine hour are utilized to estimate the GSR for the years 2009 and 2010 in the Simara Airport. The annual average solar insolation 4.62 and 4.56 k/m2/day is found at Simara Airport for years 2009 and 2010. The performance of each model was analyzed by calculating Root Mean Square Error (RMSE), Coefficient of Determination (R2) Mean Bias Error (MBE), and Mean Percent Error (MPE). The finding empirical constants 0.30 and 0.52 can be utilized to estimate the GSR where there is no measured data of GSR at similar meteorological sites of Nepal. Journal of the Institute of Engineering, 2018, 14(1): 143-150